Merothrips meridionalis sp.n. (Thysanoptera: Merothripidae), a new fungivorous species from subtropical South America - Cavalleri, Adriano; Lindner, Mariana Flores; O’donnell, Cheryle A. (Zootaxa, 2019)
We here describe Merothrips meridionalis sp.n. based on specimens originally treated by J.D. Hood as an apterous form of M. mirus. The available data on the distribution of this new species suggest that it is widespread through Brazil, living in sympatry with M. floridensis, M. mirus and M. tympanis. However, the distribution of this new species is possibly further south than other Merothripidae species recorded from South America.